2012
DOI: 10.1051/epjconf/20123302001
|View full text |Cite
|
Sign up to set email alerts
|

TBCs for Gas Turbines under Thermomechanical Loadings: Failure Behaviour and Life Prediction

Abstract: Abstract. The present contribution gives an overview about recent research on a thermal barrier coating (TBC) system consisted of (i) an intermetallic MCrAlY-alloy Bondcoat (BC) applied by vacuum plasma spraying (VPS) and (ii) an Yttria Stabilised Zirconia (YSZ) top coat air plasma sprayed (APS) at Forschungszentrum Juelich, Institute of Energy and Climate Research (IEK-1). The influence of high temperature dwell time, maximum and minimum temperature on crack growth kinetics during thermal cycling of such plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Consistently, the enhancement of crack length, due to crack coalescence as discussed above, must in turn result in a correlated decrease of the crack density. Comparable results were given by Beck et al [57], reporting a half-life threshold of 60 cracks per mm and a length of 40 lm, slightly lower.…”
Section: Failure Modes and Lifetimesupporting
confidence: 70%
See 2 more Smart Citations
“…Consistently, the enhancement of crack length, due to crack coalescence as discussed above, must in turn result in a correlated decrease of the crack density. Comparable results were given by Beck et al [57], reporting a half-life threshold of 60 cracks per mm and a length of 40 lm, slightly lower.…”
Section: Failure Modes and Lifetimesupporting
confidence: 70%
“…Following this initial degradation, crack lengths stabilize indicating a huge decrease in crack growth rate until half-life (50%) from which a roughly exponential increase of crack length, corresponding to some coalescence, controls the overall damage of the TBC, leading to final failure. Other studies have reported the same trend of crack growth as function of the fraction of life [46,57].…”
Section: Failure Modes and Lifetimesupporting
confidence: 65%
See 1 more Smart Citation
“…The other alumina phases (γ, θ, and δ) are metastable and non‐protective . The non‐alumina oxides like, Cr 2 O 3 and NiO, tend to nucleate, grow and eventually react to form undesirable porous, brittle, and rapidly growing spinel, NiCr 2 O 4 /NiAl 2 O 4 , resulting in high local residual stresses generation, which accelerates TBC failure mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…These techniques produce coatings with initial oxide layer, depending on the Al content within bond coat, which accelerates Al depletion . After the depletion of the Al in the bond coat, other non‐protective scales will start to form . Initial formed phases of the TGO are considered a critical factor influencing the life of the TBC system.…”
Section: Introductionmentioning
confidence: 99%